2017
DOI: 10.1002/oby.21950
|View full text |Cite
|
Sign up to set email alerts
|

miRNA Signatures of Insulin Resistance in Obesity

Abstract: ObjectivesExtracellular microRNAs represent functional biomarkers for obesity and related disorders; we investigated plasma microRNAs in insulin resistance phenotypes in obesity.Methods175 microRNA were analysed in females with (insulin sensitivity n=11; insulin resistance n=19; Type-II diabetes n=15) and without (n=12) obesity. Correlations between microRNA level and clinical parameters, and levels of 15 microRNA in a murine obesity model were investigated.Results106 microRNA were significantly (adjusted P≤0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
117
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 122 publications
(127 citation statements)
references
References 40 publications
(53 reference statements)
5
117
0
2
Order By: Relevance
“…Recently, this miRNA was associated with the prediction of liver dysfunction after liver resection [48]. Furthermore, previous publications suggested a role for hsa-miR-122 as a biomarker for obesity [49]. Here we were able to demonstrate that patients showed reduced levels of hsa-miR122 1 year after RYGB surgery regardless of diabetic status.…”
Section: Discussionsupporting
confidence: 65%
“…Recently, this miRNA was associated with the prediction of liver dysfunction after liver resection [48]. Furthermore, previous publications suggested a role for hsa-miR-122 as a biomarker for obesity [49]. Here we were able to demonstrate that patients showed reduced levels of hsa-miR122 1 year after RYGB surgery regardless of diabetic status.…”
Section: Discussionsupporting
confidence: 65%
“…miR‐144‐5p, first discovered to be a potential biomarker of follicular thyroid cancer, may also be a regulatory factor in various disease, including metabolic disease (metabolic syndrome and diabetes), malignant tumour (non‐small‐cell lung cancer, breast cancer, bladder cancer, oesophageal carcinoma and gastric cancer), inflammatory diseases (tuberculosis, obesity and amyotrophic lateral sclerosis), Alzheimer's disease, depressive disorders and coronary syndrome . miR‐144‐5p inhibited antibacterial autophagy and the immune response to Mycobacterium tuberculosis via repressing DNA damage‐regulated autophagy modulator 2, which is a coordinator of antimicrobial autophagy …”
Section: Discussionmentioning
confidence: 99%
“…Regarding miR-532-5p as a candidate marker for training performance outcome after carbohydrate uptake, an independent study by Cui et al found that miR-532-5p was de-regulated in participants conducting muscular strength endurance training, and it showed a negative correlation with the insulin-like growth factor-1 [26]. Moreover, several earlier publications investigated the prominent role of miR-532-5p in the context of adult obesity and diabetes type 2, in particular insulin resistance [27,28,29,30]. Interestingly, most of these studies have in common that miR-532-5p is down-regulated in patients suffering from obesity or diabetes.…”
Section: Discussionmentioning
confidence: 99%